2011
DOI: 10.1177/0194599811408554
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Node Biopsy for Head and Neck Melanoma

Abstract: Objective. This systematic review was conducted to examine the test performance of sentinel node biopsy in head and neck melanoma, including the identification rate and false-negative rate.Data Sources. PubMed, EMBASE, ASCO, and SSO database searches were conducted to identify studies fulfilling the following inclusion criteria: sentinel node biopsy was performed, lesions were located on the head and neck, and recurrence data for both metastatic and nonmetastatic patients were reported.Review Methods. Dual-bli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
3
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(70 citation statements)
references
References 49 publications
5
59
3
3
Order By: Relevance
“…In the head and neck area, the procedure is more challenging because of the intricacy of lymphatic drainage patterns, the complexity of the local anatomy and the shine-through phenomenon [41,42]. However, an SLN detection rate of 95.2 % has been reported [43], which can be improved by additional dynamic lymphoscintigraphy [44] preoperative SPECT/CT and the intraoperative use of the gamma probe [45].…”
Section: Indicationsmentioning
confidence: 99%
“…In the head and neck area, the procedure is more challenging because of the intricacy of lymphatic drainage patterns, the complexity of the local anatomy and the shine-through phenomenon [41,42]. However, an SLN detection rate of 95.2 % has been reported [43], which can be improved by additional dynamic lymphoscintigraphy [44] preoperative SPECT/CT and the intraoperative use of the gamma probe [45].…”
Section: Indicationsmentioning
confidence: 99%
“…It can be identified by dye, gamma probe, lymphoscintigraphy or a combination at a rate of 94% [11]. SLNs may contain macrometastases, which are evident on exam or imaging, or sub-clinical micrometasteses.…”
Section: Introductionmentioning
confidence: 99%
“…Mortality rates among head and neck melanomas differ by site: lesions of the scalp and neck have the highest mortality, with a 10-year survival of 60%. Tumors located on the ear, face, and eyelid have 10-year survival rates of 70, 80 and 90%, respectively [22,23]. Advanced age, male sex, nodular morphological features, tumor thickness, ulceration, and Clark level V carry a significant risk of death for cutaneous head and neck melanoma, whereas facial melanomas have a favorable prognosis [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, the combination of preoperative US and US-guided FNA cytology can identify 65% of SN metastases and thus reduce the need for surgical SN procedures [25]. De Rosa et al [22] reported a highly successful identification (93.4%) of the SN in head and neck melanoma. However, despite the technical success, this procedure results in an elevated false-negative rate (20.4%) compared with non-head and neck lesions.…”
Section: Discussionmentioning
confidence: 99%